A Political Theory of Muslim Democracy - Altuntaş Çakir, Ravza (Edinburgh University Press, 2022)
Proposes a framework of Muslim democracy that reconciles public claims made by Muslims with the normative and practical demands of democratic regimes • Constructs a Muslim democracy framework, inspired by Muslim and Western multiculturalist political thought • Provides an inclusive typology of Muslim political thought to discover essential norms for democratic thinking • Provides an inclusive typology of multiculturalism elaborating upon its capacity to reconcile democracy with religion • Synthesises these theoretical concepts and values to provide interpretative tools for a comparative political of Muslim democracy • Provides a scholarly construction of the notion of a political theory of Muslim democracy Ravza Altuntaş-Çakir examines the ideals, institutions and processes that shape the development of a concrete Muslim-based democratic system - a form of democracy that recognises the centrality of religion in Muslim societies. Questioning the customary characterisations of Islam’s compatibility with democracy, the book adopts a comparative political theory approach that initiates a dialogue between Muslim and Western political thought. It systematically studies debates concerning Muslim political thought, multiculturalism, secularism, the public sphere and constitutionalism, which enables an exploration of Muslim democracy through a political theory approach, rather than a theological one.